2009 IEEE 12th International Conference on Computer Vision Workshops, ICCV Workshops 2009
DOI: 10.1109/iccvw.2009.5457666
|View full text |Cite
|
Sign up to set email alerts
|

Learning mixed-state Markov models for statistical motion texture tracking

Abstract: A motion texture is the instantaneous scalar map of apparent motion values extracted from a dynamic or temporal texture. It is mostly displayed by natural scene elements (fire, smoke, water) but also involves more general textured motion patterns (eg. a crowd of people, a flock). In this work we are interested in the modeling and tracking of motion textures. Experimentally we observe that such motion maps exhibit values of a mixed type: a discrete component at zero and a continuous component of non-null motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This type of stochastic models can be successfully applied in various contexts, from dynamic texture classification to motion segmentation [9] or tracking [8]. However, not unlike optical flow, LDS must respect constraints which are not easily satisfied in complex natural scenes.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…This type of stochastic models can be successfully applied in various contexts, from dynamic texture classification to motion segmentation [9] or tracking [8]. However, not unlike optical flow, LDS must respect constraints which are not easily satisfied in complex natural scenes.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…It is demonstrated that the normal flow scalar motion observations extracted from these video sequences, show a discrete value at zero (null-motion) and a Gaussian continuous distribution for the rest of the values. This model was extended in Crivelli et al (2006Crivelli et al ( , 2009 and applied to the problems of motion texture segmentation, recognition and tracking. For these applications, the issue is different than for simultaneous decisionestimation problems.…”
Section: Related Work and Connectionsmentioning
confidence: 99%
“…In order to explicitly model texture dynamics, linear dynamical systems (LDS) have been proposed in [32]. Such stochastic models have been successfully applied in various contexts, from dynamic texture classification to motion segmentation [6] or tacking [5]. However, LDS is intrinsically limited by the first-order markov property and linearity assumption.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…To do this, we consider N training videos of duration T on a p × p grid as illustrated in red in figure 2. We define v n xy (t) 5 as the V1 feature for video n at spatial position (x, y) and time t. We compute all possible features v n xy (t) and compute the temporal derivativesv n xy (t). The temporal covariance matrix of equation 2 is then computed by…”
Section: Learning Local Motion Features With Sfamentioning
confidence: 99%